(untitled) (Journal of Governance and Development (JGD), 2005)
The new global epidemic highlights the accounting and financial practices of the accountants and the auditors. The vices range from overstating profits to outright criminal behavior of diverting company funds. One symptom of its pervasiveness is how fast one event in a particular part of the globe spreads to the rest of the world including Malaysia. When accountants and auditors fail to discharge their fiduciary responsibilities competently and appear not to demonstrate the highest ethical practices, the damage cuts to the very core of the capitalist financial system. A common problem is the potential conflict between the accountant’s traditional roles. The accounting fraternity, like any other important element in the capital markets, must also be accountable, responsible and transparent. The problem in Malaysia is not due to insufficient rules or regulations but rather lack of consistent enforcement of those rules. Such body can have the authority to regulate all accounting practices and professional behaviour in Malaysia. It should also have the power to conduct inquiries and make reprimands and acting as the sole authority to set standards of behaviour and code of conduct for the accounting and auditing fraternity in Malaysia.